The Effect of Verbal Stimulation Intervention and Al-Qur'an Murotal Therapy on Motor Response Changes in Patients with Decreased Consciousness - Mohri Mitra Arifin; Hikmah Lia Basuni (INDOGENIUS, 2026)
Background & Objective: Decreased consciousness is one of the signs of cerebral perfusion disorders that we often find in patients with head injuries. Head injuries are traumatic disorders of brain function, accompanied by interstitial bleeding in the brain substance without disrupting brain continuity. According to the WHO, 69 million people worldwide experience head injuries each year. Africa and Southeast Asia have the highest number of cases at 56%, while North America has the lowest at 25%. In Indonesia, based on the Basic Health Research report, head injury ranks third among the most common injuries, with a percentage of 11.9%. The purpose of this study is to determine the motor response in patients with decreased consciousness following verbal stimulation and Quranic recitation interventions. Method: A case study of patients with severe head injuries and decreased consciousness involving non-pharmacological interventions with verbal stimulation and Al-Qur'an murotal therapy on motor response changes conducted daily for 7 days of treatment with each session lasting 30 minutes per day. Result: After verbal stimulation intervention by telling stories and listening to the recitation of Surah Al-Fatihah and Surah Yasin from the Qur'an for 30 minutes, there was a change in the motor response of patients with decreased consciousness, which was evaluated by assessing the GCS. Conclusion: Verbal stimulation intervention through storytelling and recitation of the Qur'an has an effect on changes in motor responses in patients with decreased consciousness.